Correlation of maternal lipid profile with newborn’s lipid profile - Gora, Anamika; Dev, Deveshwar; Gupta, Palak; Gupta, M. L. (International Journal of Contemporary Pediatrics, 2018)
Background: Atherosclerotic cardiovascular disease (CVD) is a major cause for morbidity and mortality in the adult population. Altered lipid levels are the recognized factors. This process is considered to begin in early life and progress silently over decades. Maternal lipid concentrations may exert an in-utero influence on infant’s lipid profile. The objective of the study was to find out the correlation of maternal lipid profile with newborn’s lipid profile. Methods: This is a hospital based, cross sectional study. After applying inclusion and exclusion criteria, a total of 220 parturients and their respective newborns were enrolled. Out of 220 newborns, 110 were <2.5 kg (group A) and 110 were ≥2.5kg (group B) babies. 2.5 ml of Cord blood sample from each of enrolled newborns was collected from the placental end of the cord just after the delivery. Blood samples from the parturients were collected right after delivery. The concentrations of total cholesterol, triglycerides and HDL-c were determined by an enzymatic colorimetric method and LDL-c was calculated by the Friedewald formula. Results: In present study there was a statistically significant but poor negative correlation between maternal TG and babies’ TG level among low birth weight (˂2.5kg) babies and no other significant correlation was observed between maternal lipid profile and newborn’s lipid profile. Conclusions: Change in maternal lipid profile is not significantly associated with the mean concentrations of total cholesterol, LDL-c, HDL-c and triglycerides in newborns. Hence it shows that neonatal lipogenesis may be independent of maternal lipogenesis.